The Influence Of Emotions, Motivation And Self-Control On Athlete Concentration At Sakato Semen Padang College - Muhammada Nur Sya’ban; Anton Komaini; Tjung Hauw Sin; Wilda Welis (JETL (Journal of Education, Teaching and Learning), 2025)
The problem in this research is the athlete's lack of concentration when competing during the pandemic. The aim of this research is to determine the direct and indirect influence of emotional levels, motivation and self-control on athletes' concentration. This type of research is correlational using the path analysis method. The population in this study were female athletes, sampling used purposive sampling, totaling 30 female athletes. The test instrument used was a Likert scale questionnaire of emotionality, motivation, self-control and concentration. The data analysis technique uses Path Analysis with α = 0.05. The results of the research are: (1) There is a direct emotional influence on athlete concentration during the pandemic at the Sakato Minang Kabau training in Padang City, which is 9.12%. (2) There is a direct effect of motivation on the concentration of athletes during the pandemic at the Sakato Minang Kabau Training Center, Padang City, which is 6.30%. (3) There is a direct influence of the Self-Mastery variable on Athlete Concentration during the pandemic at the Sakato Minang Kabau Training Center, Padang City, which is 9.24%. (4) There is an indirect influence of Emotion on Concentration through Self-Mastery of 16.81%. (5) There is an indirect effect of motivation on concentration through style of 8.35%. (6) There is an indirect influence of Emotion on Concentration of 15.1%.